PEMANFAATAN MEDIA TELEVISI DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) - Gunawan, Rudy (MAJALAH ILMIAH WIDYA, 2012)
Television is a visual audio (heard and seen) electronic media, which can provide information such as news and entertainmentincluding educational materials. The objective of this paper is to find out how media education is needed to help teachers to developtheir students understanding of social studies materials. The method used is a descriptive analytical study of literature. It can beconcluded that the television media has a broad impact in diversifying the media or multi media applications. IPS will be more meaningfullearning when using the media of television effectively and efficiently.